2021
DOI: 10.1111/jace.17759
|View full text |Cite
|
Sign up to set email alerts
|

Thermal strengthening of low‐expansion glasses and thin‐walled glass products by ultra‐fast heat extraction

Abstract: Mechanical performance and consumer product safety have been major drivers for glass research and innovation. Commodity glass materials are brittle and, thus, their mechanical performance is extremely sensitive to the presence of microscopic flaws and defects at their surface: the extent by which surface flaws reduce the practical strength of glass products exceeds the effect of any optimization in glass composition by several orders of magnitude. 1 Strength-reducing flaws are created already during glass manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Most prominently, thermal or chemical strengthening are widely employed to impose a surface compressive layer which counteracts tensile loading [9]. Thermal strengthening requires relatively thick glass sheet (or container walls) and rapid quenching of the surface of a hot glass product [13], for example to be used as solar covers, safety windows or in roof-top applications. Chemically strengthened glasses are produced by diffusive exchange of the mobile alkali ions (IOX) present in the precursor glass through immersion of the glass in a bath of molten salt.…”
Section: Introductionmentioning
confidence: 99%
“…Most prominently, thermal or chemical strengthening are widely employed to impose a surface compressive layer which counteracts tensile loading [9]. Thermal strengthening requires relatively thick glass sheet (or container walls) and rapid quenching of the surface of a hot glass product [13], for example to be used as solar covers, safety windows or in roof-top applications. Chemically strengthened glasses are produced by diffusive exchange of the mobile alkali ions (IOX) present in the precursor glass through immersion of the glass in a bath of molten salt.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while higher packing density—such as achieved by slower cooling [ 48 ] or cooling under pressure [ 49 ] —would facilitate plastic deformation in principle, it was also found that rejuvenation by rapid quenching facilitates material deformation through structural compaction, leading to higher defect resistance. [ 8,50 ] Furthermore, additional p,T‐dependent reactions may occur, such as the tetrahedral‐to‐trigonal coordination transition of borate species. [ 51 ] In the case of borate‐containing glasses, such reactions may significantly reduce the stress threshold for shear deformation.…”
Section: Brittleness Intrinsic Strength and Defect Propensity Of Sili...mentioning
confidence: 99%
“…[3] As another example, roll-to-roll processing of ultrathin and flexible glass substrates has been made possible; [4,5] advanced dicing and postprocessing techniques have led to defect-free and, thus, strong edges to withstand bending loads. [6,7] Thermal tempering has been enabled for thin-walled glass products, [8] usable in glass-glass solar modules, flexible mirror substrates, quadruple-glazing, and lightweight glass containers. Optical fibers with enhanced bending resistance (both mechanical and in terms of optical loss) are used for fiber-to-the-X as well as short-haul light transmission techniques, or even suggested for integration as a functional component within textile structures.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, B 2 O 3 is of particular importance, given its pivotal role for a wide variety of specialty glasses. 25 In this context, technologies for strengthening of thin borosilicate glasses, including thermal strengthening via liquid metal immersion, 26 as well as chemical strengthening, [27][28][29] have recently received renewed interest.…”
Section: Introductionmentioning
confidence: 99%